Namudzaj At-Taqyiimi Al-Waq'i Fii Ta'limi Al-Lughah Al-Arabiyah Bimadrasati AL-Ibtidaiyati Al-Hukumiyati BiBaraya Lumbuk Al-Wustho - Lalu Muhammad Mansur (The Center for Language Development, Mataram State Islamic University., 2021)
This research uses descriptive research and data collection is done by the method of observation, documentation, and interview, all of which answer the problem of research on Authentic Assessment Model In Arabic Language Learning at the State Islamic Elementary Praya Central Lombok. The key informants in the research are Principals and fifth-grade Arabic teachers. Based on the research results, the conclusion about the model of authentic assessment in learning Arabic at the State Islamic Elementary Praya Central Lombok is 1) Find models of the three domains that were assessed namely cognitive, affective, and psychomotor. 2) Make a model of assessment rubrics for each Evaluation competence. Here is coverage that assessed the competence of the three domains, namely (1) Cognitive Domains include oral test in class, multiple-choice, objective description, description of non-objective, short answer, matching, performance / performance, and portfolios. (2) The sphere of Affective includes attitudes and interest in the Arabic language lessons, (3) Psychomotor Domains include paper and pencil tests and test performance (work samples).